Analisis Kinerja Algoritma Naive Bayes dalam Klasifikasi Data Kategorikal Prediksi Keputusan Bermain Tenis Berdasarkan Cuaca - Feriandri Lesmana; Athila Defian Rizkimu; Muhamad Ridwan Nurrulloh; Maulana Farras Fathurrahman; Abdul Habib Hasibuan; Maulana Fansyuri (PT Jurnal Cendekia Indonesi, 2025)
Decision-making based on weather factors is often subjective and inconsistent. This research applies data mining classification methods to build an objective predictive model regarding the decision to play tennis based on weather conditions. The objective of this study is to analyze the performance of the Naive Bayes algorithm in predicting this decision. The methodology involves applying the Naive Bayes algorithm to the classic